KESULITAN MEMBACA PERMULAAN SISWA KELAS II DI SEKOLAH DASAR NEGERI 83 PEKANBARU - Mira Yolanda; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to find out how difficult it was for students to read and how the efforts made by the teacher in overcoming reading difficulties for class II students at Public Elementary School 83 Pekanbaru. Reading difficulty is an unsatisfactory aspect of students' reading ability. Lower graders seem to have a lot of difficulties related to reading skills. The type of research used in this research is to use a case study approach and data collection techniques conducted interviews, observation and documentation. The results of the study showed that there were 4 students who had difficulty reading. The types of difficulties experienced by students were difficulty in spelling, difficulty in pronouncing letters, often forgetting letters, and difficulty distinguishing. Efforts made by the teacher in overcoming reading difficulties for class II students at Public Elementary School 83 Pekanbaru, namely using interesting and effective learning media, providing support and motivation, giving additional hours and lending reading books to students who are not yet fluent in reading. Factors causing children's reading difficulties include a lack of interest in reading, a lack of extra time at school, and a lack of parental guidance at home.